Is changing footstrike pattern beneficial to runners? - Joseph Hamill; Allison H. Gruber (Elsevier, 2017)
Some researchers, running instructors, and coaches have suggested that the "optimal" footstrike pattern to improve performance and reduce running injuries is to land using a mid- or forefoot strike. Thus, it has been recommended that runners who use a rearfoot strike would benefit by changing their footstrike although there is little scientific evidence for suggesting such a change. The rearfoot strike is clearly more prevalent. The major reasons often given for changing to a mid- or forefoot strike are (1) it is more economical; (2) there is a reduction in the impact peak and loading rate of the vertical component of the ground reaction force; and (3) there is a reduction in the risk of a running-related injuries. In this paper, we critique these 3 suggestions and provide alternate explanations that may provide contradictory evidence for altering one's footstrike pattern. We have concluded, based on examining the research literature, that changing to a mid- or forefoot strike does not improve running economy, does not eliminate an impact at the foot-ground contact, and does not reduce the risk of running-related injuries.